Spatialization of soil quality index in the Sub-Basin of Posses, Extrema, Minas Gerais - Gabriela C. Lima; Marx L. N. Silva; Diego A. F. de Freitas; Bernardo M. Cândido; Nilton Curi; Marcelo S. de Oliveira (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to determine and spatialize the soil quality index (SQI), in relation to chemical and physical attributes, and evaluate its use in the payment for environmental services in the Sub-Basin of Posses, Extrema-MG, Brazil, which represents the Atlantic Forest Biome. SQI values were influenced by both the replacement of native forests by stands of eucalyptus and by pastures and annual crops, reflecting in the reduction of soil quality in the sampled layer in the evaluated systems. The spatialization of SQI showed values ranging from 0.40 to 0.80, with some specific areas with high values and others with values above 1.00 (native forest). The reforestation with eucalyptus conditioned most of the soils with low chemical and physical deterioration, due to accumulation of litter. The lowest SQI values are associated with pastures. SQI adjusted to the exponential model, which allowed the use of ordinary Kriging. The SQI has a great potential of use in the payment to farmers who provide services of soil and water conservation.